Identifikasi Wanda Janaka berbasis Deep Learning dengan Metode Convolutional Neural Network - Benedictus Herry Suharto; Mawar Hardiyanti (Computer Science Research and Its Development Journal, 2023)
UNESCO named Wayang Kulit a "Masterpiece of Oral Intangible Heritage of Humanity" for Indonesian traditional arts. Wayang Kulit's characters show a symbol of personality, identity, image, appearance, and quality of the characters. In certain situations in the Wayang Kulit performance scene, this character has a different appearance image called Wanda. Wanda Wayang Kulit is less well-known among the younger generation. Therefore, technological creativity is needed so the younger generation can distinguish Wanda Wayang Kulit as part of the Indonesian nation's artistic and cultural literacy. One of the potential technologies that can be used is a smartphone application based on Deep Learning CNN to detect and recognize Wanda Wayang Kulit. In contrast to previous studies that have successfully used Deep Learning CNN to recognize Wayang Kulit characters, this research aims to create a CNN Deep Learning model to classify Wanda Wayang Kulit Janaka. The model uses five Wanda Wayang Kulit Janaka images from an Android smartphone camera. The results achieved from this study are the CNN deep learning model, which can classify the image of Wanda Wayang Kulit Janaka using an Android smartphone camera with an accuracy of 84%.